Anaphylaxis to simultaneous administration of inactivated tissue culture hepatitis A vaccine and purified chick embryo cell rabies vaccine after multiple doses. Issue 1 (27th January 2021) - Hasegawa, Kohei; Ohji, Goh; Iwata, Kentaro
Abstract : Both the inactivated hepatitis A vaccine (Aimmugen) and purified chick embryo cell rabies vaccine (PCECV, Rabipur) are well tolerated. Anaphylaxis has rarely been reported as an adverse reaction of these vaccines. There have been no reports or published case reports of anaphylaxis due to Aimmugen. According to the Japanese Ministry of Health, Labour and Welfare Aimmugen adverse reaction report, no cases of anaphylaxis have been reported from April 2013 to August 2016. Twenty cases of anaphylaxis due to PCECV (RabAvert) have been reported from 1997 to 2005 in USA, whereas 2 cases have been reported from 2006 to 2016. We report a case of anaphylaxis after multiple vaccinations in a 24-year-old man with ulcerative colitis, previous medical history of tonsillectomy for IgA nephropathy and no history of allergies.